APLIKASI MODEL PEMBELAJARAN COOPERATIVE SCRIPT UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA DIKLAT MENGGUNAKAN HASIL PENGUKURAN - Oriza Candra; Doni Tri Putra Yanto; Nazirul Imam (Perspektif Pendidikan dan Keguruan, 2020)
Student learning outcomes in learning is very important to be used as a reference for indicate of successful in learning. The observation result at grade X TITL SMKN 1 Pariaman identified that there are several problems that influence student learning outcomes, such as communication in learning process just one - way, the students did not master the contents, students tend to be afraid to ask the question, the students out of the classroom and talk with their seatmate. Consequently most of student learning outcomes were under KKM that seen from the pretest. To overcome this problem, research is conducted which seeks to see an increase in student learning outcomes in subjects " Using the Measurement Results " in Learning Model Cooperative Script at grade X TITL SMKN 1 Pariaman. Type of this research was quasi experiment with one group pretest – posttest design. Subjects were students at grade X TITL SMKN 1 Pariaman for 2014/2015 academic year that consists of 40 students. Data were collected through the test of pretest - posttest results, 40 objective questions for the pretest and 34 objective questions for the posttest. Improving student learning outcomes calculated by the formula Gain Score of pretest - posttest. This research indicated that there is an increase in student learning outcomes in subjects “Using Measurement Results” in Learning Model Cooperative Script at grade X TITL SMKN 1 Pariaman.